Corpus-based critical discourse analysis of reporting practices in English news reports on public health event in China and United States - Li, Zhuoran; Zhao, Ronghui; Lou, Baocui (Frontiers in Psychology, 2023)
Reporting speech is a basic form of human language, and reporting practices play a key role in news report. As one of the important rhetorical devices to introduce the reported speech, reporting verbs can help the readers understand the source of the reported speech and the attitude of the journalist or the media towards the reported information. This study examines the features of reporting practice in Chinese and American news reports on public health emergency by investigating the use of reporting verbs from the perspective of critical discourse analysis. It is found that Chinese and American news reports tend to use the same high-frequency reporting verbs in reporting the COVID-19 pandemic. Chinese and American news corpora show difference in the distribution feature of high-frequency reporting verbs in terms of semantic category. Both Chinese and American news reports use speech reporting verbs most frequently, indicating an objective attitude towards the reported event, and use speech reporting verbs and speech act reporting verbs to introduce the reported speech with comparatively higher degree of certainty. American news reports also frequently use mental reporting verbs to show the attitude of uncertainty toward the reported speech. The findings of this study can provide insights into the research on reporting strategies of news reports on emergencies in China for foreign audience.